O esporte na Educação Física Escolar sul-americana: uma análise dos sentidos emergentes de documentos curriculares da Argentina, Brasil, Chile e Uruguai - Baroni, Ana Beatriz Sgotti (Universidade Federal de São Carlos, 2025)
The study in question aims to analyze the meanings attributed to sports in school physical education in Argentina, Brazil, Chile, and Uruguay, based on the national curriculum documents of each country. The research was motivated by participation in the course "Physical Education in Latin American Pedagogical Contexts" and the interest in understanding how sports are portrayed in some South American countries. Throughout the work, the concepts of decolonial education, school physical education, and sports in Brazilian physical education will be presented, which help in understanding the topics addressed. This qualitative study was carried out using the documentary analysis method of the main national documents from each of the mentioned countries. The results found highlighted the multiple meanings attributed to sports in South American school physical education, mainly marked by the cultural influence of each country, which made it possible to understand the role of education physical education in the comprehensive development of students.
Sport in South American School Physical Education: an analysis of the emerging meanings in curricular documents from Argentina, Brazil, Chile, and Uruguay
Keywords: Educação Física Escolar; Esporte; Currículo; América do Sul; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade